Młodzi o młodości - definiowanie młodości i cech osobowościowych młodzieży w kontekście współczesnych wyzwań = The youth about youth - defining youth and personality traits of young people in the context of contemporary challenges - Broszkiewicz, Wojciech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author of the paper focused on the attempt (via the questionnaire survey) to obtain the answers to the following questions: How do the youth define the period of youth? Are the youth aware of the requirements of modern times? What qualities do the youth use to describe themselves? Do these characteristics correspond to those preferred in a modern society?
Keywords: youth; students; contemporary society; modern personality; młodzież; studenci; społeczeństwo współczesne; osobowość nowoczesna